ICTV Virus Taxonomy Profile: Botourmiaviridae - Ayllón, María A; Turina, Massimo; Xie, Jiatao; Nerva, Luca; Marzano, Shin-Yi Lee; Donaire, Livia; Jiang, Daohong; Consortium, Ictv Report (Journal of general virology, 2020)
The family includes viruses infecting plants and filamentous fungi containing a positive-sense, ssRNA genome that can be mono- or multi-segmented. Genera in the family include: (plant viruses), and , and (fungal viruses). This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the family , which is available at ictv.global/report/botourmiaviridae.